Cidades, territórios e estádios de futebol : uma análise do consumo do espaço no entorno do Independência e Mineirão em Belo Horizonte - André Quintão da Silva (2023)
This study aims to understand the codes, signs, and meanings attributed to the Mineirão and Independência stadiums, specifically in their use by Clube Atlético Mineiro fans who attended these spaces between 2012 and 2014. The research was based on the Lefebvrian triad of space production (lived, perceived, and imagined). Throughout the study, the physical space (lived) and the imaginative inventions of space (imagined) became important points of reference, as we adopted the integrated perspective of Rogerio Haesbaert (2020) to understand urban multi-territorialities. An articulation was also made with Néstor Garcia Canclini's discussions on cultural hybridity to reflect on continuities and discontinuities in the constitution of the spatial practices of Atletico Mineiro fans. Empirically, our interest focuses on the recent renovations of the stadiums in Belo Horizonte for the 2014 World Cup and the processes of de-re-territorialization that occurred thereafter. To do so, we used the Wayback Machine (Internet Archive) to retrieve interactions among Clube Atlético Mineiro fans on the social network Orkut, with the aim of analyzing their relationships with the outskirts of the stadiums. Within the methodological framework, 503 topics from Orkut were collected, and a total of 10 were selected for analysis, which together gathered 1,031 comments published between December 29, 2011, and October 1, 2014. When examining the phenomenon of re-territorialization among the fans, a tendency was observed to view the Independência Stadium with a certain familiarity and coziness, which can be explained by its external environment representing a closer resemblance to what is imagined for a stadium in Minas Gerais: a space for socialization, preservation of culinary traditions, and less surveillance.